Reducing Carbon Footprint in Ankara: The Use of Biodiesel Produced from Waste Oils in Public Transportation - Osman Furkan Kapıkıran; Halil İbrahim Variyenli; Mert Ökten; Semih Sadi Kılıç (Gazi Üniversitesi Fen Bilimleri Dergisi)
Biomass energy is a renewable energy source obtained by converting organic wastes and plant materials into energy. Biomass, which has an increasing importance in energy consumption in recent years, contributes to sustainability and carbon emission reduction targets as an alternative to fossil fuels. Biodiesel is derived from biomass and used as a motor fuel. Due to its renewable feature and lower carbon emission, biodiesel attracts attention as an environmentally friendly fuel alternative. This study examines the utilisation of biodiesel derived from waste oils in public transport vehicles within the province of Ankara, and the impact of this utilisation on the carbon footprint. The conversion of waste oils into biodiesel represents a promising fuel alternative that simultaneously advances environmental sustainability and fosters energy diversity. The study presents a numerical analysis of the impact of biodiesel usage on fossil fuel consumption and carbon emissions in the public transport fleet, specifically in buses. Furthermore, the impact of this practice on the local economy and its long-term implications for sustainable urban transportation are also assessed. In Ankara, 870522 liters of waste oil are collected on a monthly basis, resulting in a reduction of 76% in carbon emissions due to the production of 739943 liters of biodiesel derived from these oils. As a result, energy consumption, efficiency and carbon emission analyses show that biodiesel is an economically and environmentally sustainable alternative. It is expected that the recycling of waste oils will improve waste management and reduce the negative impacts on the environment.